2020
DOI: 10.7717/peerj.9661
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, assembly, annotation, and gene expression: novel insights into browning-resistant Luffa cylindrica

Abstract: Luffa is a kind of melon crop widely cultivated in temperate regions worldwide. Browning is one of the serious factors affecting the quality of Luffa. Therefore, the molecular mechanism of Luffa browning is of great significance to study. However, the molecular diversity of Luffa cultivars with different browning-resistant abilities has not been well elucidated. In our study, we used high-throughput sequencing to determine the transcriptome of two Luffa cylindrica cultivars ‘2D-2’ and ‘35D-7’. A total of 115,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…LcCAT1 and LcCAT2 genes were significantly expressed on the second and third day, respectively, indicating that LcCAT1 and LcCAT2 regulated CAT enzyme activity at the transcriptional level (Figure 5f,g). Ya Wang et al sequenced the fresh-cut luffa with browning resistance and browning susceptibility and analyzed the expression of the LcCAT gene family, which also confirmed our results [66]. Zhu et al sequenced fresh-cut luffa and found that CAT enzyme activity was regulated by the LcCAT1 and LcCAT2 genes [2].…”
Section: Discussionsupporting
confidence: 81%
“…LcCAT1 and LcCAT2 genes were significantly expressed on the second and third day, respectively, indicating that LcCAT1 and LcCAT2 regulated CAT enzyme activity at the transcriptional level (Figure 5f,g). Ya Wang et al sequenced the fresh-cut luffa with browning resistance and browning susceptibility and analyzed the expression of the LcCAT gene family, which also confirmed our results [66]. Zhu et al sequenced fresh-cut luffa and found that CAT enzyme activity was regulated by the LcCAT1 and LcCAT2 genes [2].…”
Section: Discussionsupporting
confidence: 81%
“…The WRKY transcription factor family, involved in ABA signaling pathway and stress signaling, is closely related to ROS production and scavenging (Chen et al, 2010; He, 2017). Also, WRKY transcription factors are involved in the fruit browning process by regulating the ROS level in Chinese walnut (Zhang et al, 2019), luffa (Wang et al, 2020), and apple (Zuo et al, 2021). The ROS level might decrease with the downregulation of WRKY60 expression during postharvest browning.…”
Section: Discussionmentioning
confidence: 99%
“…We used BLASTP (Gallin and Boutet, 2011) to retrieve 28 K + channel protein sequences from apple (Malus domestica) at NCBI (9 AKT, 4 KAT, 4 SKOR, and 11 two-pore domain potassium channel genes). Taking these 28 apple K + protein channel sequences as templates, we used Primer Premier 6.0 (Wang et al, 2020) to design specific primers and ultimately cloned 8 K + channel genes from 12-2 (Supplementary Table S1). With cDNA from 12-2 as a template, we used the high-fidelity enzyme 2 × Phanta Max Master Mix (Vazyme Biotech, Nanjing, Jiangsu, China) for PCR amplification.…”
Section: Cloning and Screening Of K + Channel Genes From 12-2mentioning
confidence: 99%